Quantitative study of microstructural, textural and hardness evolution of high-purity Ti sheet during rolling from low to medium strains. (December 2021) - Hu, Xing; Chai, Linjiang; Zhu, Yufan; Wu, Hao; Luo, Jinru; Tian, Lin; Sun, Qi; Li, Yuqiong; Cheng, Jun
Abstract: Many Ti-base products are made of sheets/plates processed by rolling and strong crystallographic textures are often developed, especially for those with α-Ti as the major phase. Compared to intensive explorations of deformation behaviors of low alloyed Ti (including commercial-purity Ti) during rolling, much less has been made for high-purity Ti (HP-Ti), in spite of acknowledged important effects of some impurities on deformation modes of α-Ti. To clearly reveal microstructural, textural and hardness evolution of HP-Ti during rolling from low to medium strains, a typical HP-Ti sheet after 10–50% cold rolling was subjected to quantitative characterization by jointly using electron backscatter diffraction, electron channel contrast imaging, X-ray diffraction and hardness test. Results show that plastic deformation readily occurs through the active operation of both slip and twinning (mainly { 11 2 ¯ 2 } < 11 2 ¯ 3 ¯ > and { 10 1 ¯ 2 } < 10 1 ¯ 1 ¯ > ) during 10–30% rolling. As a result of massive twinning, initial grain structures are markedly refined along with significant grain reorientation, leading to largely reduced textural intensity and the presence of new components. At higher strains (>30%), slip becomes the only deformation mode with new twins no longer appearing. In the 50%-rolled specimen, a bimodal basal texture similar to the initial one is formed along with a weak component of c//TD. The HP-Ti sheet is always hardened with increasing strains (from 120.8 ± 5.7 HV to 234.3 ± 5.8 HV). Quantitative analyses reveal that the grain refinement caused by dense twins at low strain (10% rolling) can lead to significant hardening contribution, which keeps relatively stable during subsequent rolling. Since slip can play a more important role with increasing strains, denser low angle boundaries are produced and gradually make larger contributions to hardening. As the rolling reduction increases to 50%, the contribution from low angle grain boundaries to hardness exceeds that from high angle grain boundaries (Hall-Petch hardening). The results documented in this work should not only be able to help clarify specific deformation mechanisms of HP-Ti, but also provide important implications for improving their properties. Graphical Abstract: ga1 Highlights: During 10–30% rolling, twinning leads to marked microstructural and textural changes. At higher strains, bimodal basal texture with c//TD component is developed by slip. Twinning-induced grain refinement at low trains can produce remarkable hardening. After 50% rolling, hardening contribution from the LABs exceeds that from the HABs.